(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
This article examines the relevance of learner-centered approaches in teaching Arabic phrase syntax to college students and explores the role of teacher training programs in promoting the adoption and implementation of these approaches. The benefits of learner-centered instruction are discussed, and the importance of teacher training in equipping educators with the necessary knowledge, skills, and strategies is emphasized. Recommendations for enhancing Arabic phrase syntax instruction are provided based on the findings of this study.